Novel non-substrate modulators of the transmembrane efflux pump P-glycoprotein (ABCB1)1. Issue 5 (13th May 2015) - Krawczyk, Sören; Baumert, Christiane; Molnár, Joséf; Ritter, Christoph; Höpner, Jens; Kloft, Charlotte; Hilgeroth, Andreas
<x xml:space="preserve">Abstract</x> Novel non-substrate modulators of the transmembrane efflux pump P-gp have been profiled as nontoxic and mdr reversing agents.